The Village Forest as A Counter Teritorialization by Village Communities in Kampar Peninsula Riau - Rahmat Budiono; Bramasto Nugroho; Hardjanto; Dodik Ridho Nurrochmat (Institut Pertanian Bogor (IPB University), 2018)
State hegemony over forest areas in practice is indeed more favorable to forestry corporations and eliminates a village community access. Data analyzed using Antonio Gramsci's hegemony theory and Laclau and Mouffe's hegemony to understand the movements of villagers to regain access to the forests. The results of this study indicate the emergence of antagonism between rural communities and companies was the impact of the abandonment of villagers from the forestry development. NGOs, as an organic intellectual has succeeded strengthen the village institutions to fight for remaining forests through permit of village forest, even though they have to compete with the biggest forestry company. The Permit of Village Forest in Kampar Peninsula has become the first social forestry permit in Riau Province. This condition is a fact the slow return of forest access to rural communities through social forestry programs. The Program of Social Forestry that was recently introduced by the state was not a counter-hegemony (victory of the villagers against state hegemony), but it is reinforcing hegemony of state over forest areas.